A porous Zn cathode for Li–CO2 batteries generating fuel-gas CO. Issue 28 (5th July 2018) - Xie, Jiafang; Liu, Qin; Huang, Yiyin; Wu, Maoxiang; Wang, Yaobing
Abstract : A porous fractal Zn cathode with high electrocatalytic activity and selectivity to CO2 -to-CO conversion enables Li–CO2 batteries that produce fuel gas CO. Abstract : Global climate change and energy concerns trigger worldwide interest in sustainable, economical CO2 reductive transformation into valuable chemicals. However, traditional electro/thermo-catalysis strategies usually consume a large amount of energy and suffer from low efficiency. Herein, a three-dimensional porous fractal Zn cathode is synthesized by redox-coupled electrodeposition and it exhibits excellent electrocatalytic properties for CO2 -to-CO conversion. Inspired by the coupling of a metal battery and CO2 electroreduction, a novel fuel-gas CO generating Li–CO2 battery is firstly realized with the as-prepared porous fractal Zn cathode. Meanwhile, CO formation can be easily tuned within a wide range of discharge currents and reach a maximum faradaic efficiency of up to 67%. Finally, based on gas and solid discharge product analysis, the related mechanism of CO main product production is proposed as 2Li + + 2CO2 + 2e − → CO + Li2 CO3 . Hence the present work presents a new way for the further development of metal–CO2 batteries to generate useful chemicals and fuels besides electrical energy.